The impact of spelling regularity on handwriting production: A coupled fMRI and kinematics study. (April 2019) - Palmis, Sarah; Velay, Jean-Luc; Fabiani, Elie; Nazarian, Bruno; Anton, Jean-Luc; Habib, Michel; Kandel, Sonia; Longcamp, Marieke
Abstract: Current models of writing assume that the orthographic processes involved in spelling retrieval and the motor processes involved in the control of the hand are independent. This view has been challenged by behavioral studies, which showed that the linguistic features of words impact motor execution during handwriting. We designed an experiment coupling functional magnetic resonance imaging and kinematic recordings during a writing to dictation task. Participants wrote orthographically regular and irregular words. The presence of an irregularity impacts both the initiation of the movement and its fine motor execution. At the brain level, the left inferior frontal and fusiform gyri, two regions belonging to the core of the written language system, were found to be sensitive to the presence of an irregularity and to its position in the word during writing execution. Moreover, the left superior parietal lobule, the left superior frontal gyrus and the right cerebellum, three motor-related regions, displayed a stronger response to irregular than regular words. These results constitute direct evidence that orthographic and motor processes occur in a continuous and interactive fashion during writing.